Peran Guru dalam Meningkatkan Keterampilan Siswa melalui ”Project Based Learning’’ untuk Mengatasi Permasalahan Pembelajaran - Salsabila Yumiati Putri; Dewi Nur Rahma; Intan Dian Silvarana; Fija Amrul Baqi (Journal on Education, 2025)
Education today is not only focused on knowledge transfer but also emphasizes the development of critical thinking, creativity, and collaboration skills. With the rapid advancement of technology and globalization, the education system is expected to produce students with extensive knowledge and skills relevant to the workforce and everyday life. This study aims to analyze the role of teachers in implementing the Project-Based Learning (PjBL) method to enhance student skills and examine its impact on their ability to complete tasks and solve problems. Using a qualitative approach with a literature study as the research subject, this study explores how teachers act as facilitators by guiding, monitoring, and providing constructive feedback in project-based learning. The findings indicate that PjBL effectively improves students' critical thinking, creativity, and collaboration skills through real-world challenges that require innovative solutions. In addition to enhancing academic and social skills, PjBL equips students with essential life skills, including the ability to utilize technology. Despite challenges in integrating learning media, PjBL has been proven to increase student engagement, responsibility, and teamwork. Therefore, this method serves as a relevant learning strategy in addressing modern educational challenges.